New regimens of benznidazole monotherapy and in combination with fosravuconazole for treatment of Chagas disease (BENDITA): a phase 2, double-blind, randomised trial - Torrico, Faustino (2021)
Background: Current treatment for Chagas disease with the only available drugs, benznidazole or nifurtimox, has substantial limitations, including long treatment duration and safety and tolerability concerns. We aimed to evaluate the efficacy and safety of new benznidazole monotherapy regimens and combinations with fosravuconazole, in the treatment of Chagas disease. Methods: We did a double-blind, double-dummy, phase 2, multicentre, randomised trial in three outpatient units in Bolivia. Adults aged 18–50 years with chronic indeterminate Chagas disease, confirmed by serological testing and positive qualitative PCR results, were randomly assigned (1:1:1:1:1:1:1) to one of seven treatment groups using a balanced block randomisation scheme with an interactive response system. Participants were assigned to benznidazole 300 mg daily for 8 weeks, 4 weeks, or 2 weeks, benznidazole 150 mg daily for 4 weeks, benznidazole 150 mg daily for 4 weeks plus fosravuconazole, benznidazole 300 mg once per week for 8 weeks plus fosravuconazole, or placebo, with a 12-month follow-up period. The primary endpoints were sustained parasitological clearance at 6 months, defined as persistent negative qualitative PCR results from end of treatment, and incidence and severity of treatment-emergent adverse events, serious adverse events, and adverse events leading to treatment discontinuation. Primary efficacy analysis was based on the intention-to-treat and per-protocol populations and secondary efficacy analyses on the per-protocol population. Safety analyses were based on the as-treated population. Recruitment is now closed. This trial is registered with ClinicalTrials.gov, NCT03378661. Findings: Between Nov 30, 2016, and July 27, 2017, we screened 518 patients, and 210 were enrolled and randomised. 30 patients (14%) were assigned to each treatment group. All 210 randomised patients were included in the intention-to-treat population, and 190 (90%) were included in the per-protocol population. In the intention-to-treat analysis, only one (3%) of 30 patients in the placebo group had sustained parasitological clearance at 6 months of follow-up. Sustained parasitological clearance at 6 months was observed in 25 (89%) of 28 patients receiving benznidazole 300 mg daily for 8 weeks (rate difference vs placebo 86% [95% CI 73–99]), 25 (89%) of 28 receiving benznidazole 300 mg daily for 4 weeks (86% [73–99]), 24 (83%) of 29 receiving benznidazole 300 mg daily for 2 weeks (79% [64–95]), 25 (83%) of 30 receiving benznidazole 150 mg daily for 4 weeks (80% [65–95]), 23 (85%) of 28 receiving benznidazole 150 mg daily for 4 weeks plus fosravuconazole (82% [67–97]), and 24 (83%) of 29 receiving benznidazole 300 mg weekly for 8 weeks plus fosravuconazole (79% [64–95]; p<0·0001 for all group comparisons with placebo). Six patients (3%) had ten serious adverse events (leukopenia [n=3], neutropenia [n=2], pyrexia, maculopapular rash, acute cholecystitis, biliary polyp, and breast cancer), eight had 12 severe adverse events (defined as interfering substantially with the patient's usual functions; elevated alanine aminotransferase [n=4], elevated gamma-glutamyltransferase [n=2], elevated aspartate aminotransferase [n=1], neutropenia [n=3], leukopenia [n=1], and breast cancer [n=1]), and 15 (7%) had adverse events that led to treatment discontinuation (most of these were in the groups who received benznidazole 300 mg daily for 8 weeks, benznidazole 300 mg once per week for 8 weeks plus fosravuconazole, and benznidazole 150 mg daily for 4 weeks plus fosravuconazole). No adverse events leading to treatment discontinuation were observed in patients treated with benznidazole 300 mg daily for 2 weeks or placebo. There were no treatment-related deaths. Interpretation: Benznidazole induced effective antiparasitic response, regardless of treatment duration, dose, or combination with fosravuconazole, and was well tolerated in adult patients with chronic Chagas disease. Shorter or reduced regimens of benznidazole could substantially improve treatment tolerability and accessibility, but further studies are needed to confirm these results. Funding: Drugs for Neglected Diseases initiative (DNDi). Translation: For the Spanish translation of the abstract see Supplementary Materials section.